On the security of Bitmap Images using Scrambling based Encryption Method - Shamsulddin Abdulsattar, Fatimah (Journal of Engineering and Sustainable Development, 2009)
Image encryption is one of the most important applications in transferring images through the internet. In most of the natural images the values of the neighboring pixels are strongly correlated. This means that the value of any given pixel can be reasonably predicted from the values of its neighbors. This paper presents an approach for image encryption based on combination of image scrambling and well known encryption and decryption algorithms such as RC4 and AES. The original image can be viewed as an arrangement of pixels, which were rearranged into a scrambled image using pseudo random index generator, and then the generated image was encrypted using one of the encryption algorithm. The results showed that the correlation between image elements was significantly decreased by the proposed technique. Also, a number of performance measuring factors were considered to show the impact of the proposed technique.